Celebrity endorsement, destination image and tourist intention to visit on tourism destination / Syed Samir Syed Omar - Syed Omar, Syed Samir (2013)
Prior to the Ministry of Tourism Malaysia mission of promoting domestic tourism by local tourist, this study encompasses in exploring one creative opportunity in promoting tourism destination which is celebrity endorsement. The relationship between celebrity endorsements, destination image and tourist intention to visit towards a tourism destination were investigated. By using self-administered questionnaire adapted from previous researchers, some of the issues of interest were obtained.Samples of 412 local tourists in Kuala Lumpur has complete the set of survey questionnaire regarding the issues in order to accomplish the objective of the study. The idea is that when celebrity endorsement is communicated towards a desired target market, it could have the ability to create positive attitude towards the destination, which in turn may have positive influence on intention to visit the destination. The results show an interesting finding whereby destination image were found mediate the relationship between celebrity endorsement and intention to visit. This study will contribute to other researcher since there are few studies on celebrity endorsement in the hospitality industry especially in Malaysia. Besides that, effectiveness of celebrity endorsement in promoting tourism destination could create a large boost in sale in hospitality industry because of the increasing number of tourist to visit a particular destination.